The Persian gamble [large type] - Rosenberg, Joel C., 1967- (Center Point Large Print, 2019)
"From the New York Times bestselling author of The Kremlin Conspiracy comes this international thriller about a terrifying nuclear alliance among three world powers--Russia, Iran, and North Korea--and the man who must halt their deadly strategy"--